Characteristics of grain quality and starch fine structure of japonica rice kernels following preharvest sprouting. (September 2020) - Zhou, Lihui; Lu, Yan; Zhang, Yadong; Zhang, Changquan; Zhao, Ling; Yao, Shu; Sun, Xuchao; Chen, Tao; Zhu, Zhen; Zhao, Qingyong; Zhao, Chunfang; Liang, Wenhua; et al.
Abstract: Preharvest sprouting (PHS) is one of the most serious defects that impacts rice production and grain quality. Knowledge about the effects of PHS on the eating and cooking quality (ECQ) of milled rice is limited. Here, we selected four japonica rice varieties to study the influences of PHS on grain quality. The results showed that PHS strongly led to poor grain appearance and the development of small starch granules whose surfaces were eroded. Analysis of starch fine structure revealed that PHS resulted in amylose (AM) degradation; in particular, PHS caused a decrease in the content of long AM chains. Moreover, PHS led to a decrease in the content of short amylopectin (AP) chains in the varieties Yandao 815 (YD815), Wuyugeng 27 (WY27) and Yangeng 13 (YG13), while the variety Sidao 785 (SD785) displayed the opposite trend. We propose that the main reasons for the decrease in starch crystallinity and the pasting profiles of the germinated rice were due to both the tendency of the AM content to decrease and the degree of this decrease in the content of the different AM chains along with changes in AP and other major components. All these changes caused by PHS led to a decrease in both ECQ and palatability of milled rice. Graphical abstract: Image 1 Highlights: Rice eating and cooking quality decreased after pre-harvest sprouting. The physicochemical properties of rice kernels were greatly affected by pre-harvest sprouting. Starch fine structures were deep causes of adverse effects of pre-harvest sprouting on grain quality.